(untitled) (Research, Society and Development, 2023)
Objective: To analyze the prevalence and possible factors associated with self-medication in the population of Bahia during the pandemic caused by Covid-19. Methods: This is an exploratory research that has a descriptive character, with a quantitative nature and approach. The research universe was composed of residents of the State of Bahia. The study was approved by the Research Ethics Committee (CEP) under protocol 4.941.863. The collected information was tabulated using Microsoft Office Excel® and the statistical analysis was carried out in a descriptive, univariate way using the Statiscal Package For Social Science (SPSS) software. Results: There were five hundred and thirty participants in this research. Among the medications contained in the questionnaire, the most used was Vitamin D, being used by 41.7% of respondents. Among the reasons for using the drug, the most prevalent was Cold/Flu with 18.4%, followed by regular consumption as cause (18.0%). Conclusion: More studies need to be carried out to confirm the effectiveness of the drugs both as prophylaxis and for the treatment of SARSCoV-2 to avoid the dissemination of information without scientific basis.